2005
DOI: 10.1016/s1808-8694(15)31236-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of chronic rhinosinusitis in patients with cystic fibrosis: correlation between anamnesis, nasal endoscopy and computed tomography

Abstract: The diagnosis of chronic rhinosinusitis was statistically different between the three methods. It was higher in imaging analysis and lower in questionnaire. The nasal endoscopy is an excellent method to evaluate nasossinusal disease in cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 28 publications
5
29
1
6
Order By: Relevance
“…Nasal and paranasal sinus CT scan revealed high prevalence of affections, in which 49 out of 50 patients presented at least one affection. These data are in accordance with other studies that assessed CT scan findings in CF patients [4,6,7,12,14]. However, few studies have correlated the abnormalities found in upper airway CT scans with genotype and severity of the disease.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nasal and paranasal sinus CT scan revealed high prevalence of affections, in which 49 out of 50 patients presented at least one affection. These data are in accordance with other studies that assessed CT scan findings in CF patients [4,6,7,12,14]. However, few studies have correlated the abnormalities found in upper airway CT scans with genotype and severity of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of this finding is about 57% [12,14,15], quite close to our prevalence data of 58%. It is not clear whether bulging corresponds to pseudomucocele, detected by paranasal sinuses CT scan.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In asymptomatic adult patients, Havas et al, 25 evaluating CT scans of the skull, found 42% of abnormalities in 1 or more paranasal sinus and the thickness growth of the mucosa of the ethmoidal sinus was the alteration more frequently identified. In studies with patients aged from 6 years to 22 years, Boari and Castro Jú nior 26 found radiographic opacification of the paranasal sinus in 93% of the cases; only 20% were symptomatic, and they concluded that diagnosis of the chronic rhinosinusitis was superior in the analyses carried out through image exam in relation to anamnese. The causes of mucosa thickness growth or a b 26 or by another factor that has led to the inflammation of the mucosa, such as asthma, rhinitis, chemical products and viral or bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In studies with patients aged from 6 years to 22 years, Boari and Castro Jú nior 26 found radiographic opacification of the paranasal sinus in 93% of the cases; only 20% were symptomatic, and they concluded that diagnosis of the chronic rhinosinusitis was superior in the analyses carried out through image exam in relation to anamnese. The causes of mucosa thickness growth or a b 26 or by another factor that has led to the inflammation of the mucosa, such as asthma, rhinitis, chemical products and viral or bacterial infections. 27 The fact that the patients belong to the same family and coexist in one environment may justify the fact that all present alterations are in the paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%